2022
DOI: 10.1136/jitc-2022-004699
|View full text |Cite|
|
Sign up to set email alerts
|

Reversal of immune-checkpoint inhibitor fulminant myocarditis using personalized-dose-adjusted abatacept and ruxolitinib: proof of concept

Abstract: Immune-checkpoint inhibitors (ICI) have revolutionized cancer therapy but are associated with infrequent but lethal myocarditis, for which management remains uncertain. Abatacept, a CTLA-4 fusion protein targeting CD86 on antigen presenting cells and leading to global T-cell anergy, has been described as a potential treatment in individual reports. Yet, abatacept treatment dosage, schedule and optimal combination with other immunosuppressive therapies are unclear. We describe a 25-year-old man who developed pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 11 publications
2
35
0
Order By: Relevance
“…However, the risk of tumor relapse should also be noted. Two patients experienced tumor relapse 3 months and 4 months after abatacept treatment, respectively (96,97). The duration of follow-up was only 1 month in another patient, the possibility of tumor relapse could not be excluded (94).…”
Section: Ctla-4 Agonistsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the risk of tumor relapse should also be noted. Two patients experienced tumor relapse 3 months and 4 months after abatacept treatment, respectively (96,97). The duration of follow-up was only 1 month in another patient, the possibility of tumor relapse could not be excluded (94).…”
Section: Ctla-4 Agonistsmentioning
confidence: 96%
“…Methylprednisolone 1g/d and addition of mycophenolatemofetil had limited efficacy. Initiation of abatacept and ruxolitinib reversed the disease course and the patient fully recovered clinically, with ejection fraction restoring to 60% (97). Therefore, use of abatacept in ICI-induced myocarditis is worth expecting, especially considering its efficacy in concurrent myositis and myocarditis.…”
Section: Ctla-4 Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a mouse model of ICI-induced myocarditis, abatacept reduced immune system activation and increased survival [ 66 , 67 ]. Several clinical studies reported the administration of abatacept in ICI-induced myocarditis [ 68 , 69 , 70 ], with promising results obtained, in particular in the simultaneous treatment of myositis and myocarditis. However, the risk of cancer relapse should also be noted.…”
Section: Management Of Ici-related Cardiotoxicitymentioning
confidence: 99%
“…Immune modulators which have been shown in case reports or small case series to be effective in reversing near-lethal ICI-myocarditis. Drugs which have been investigated include tocilizumab (IL-6R antibody) (145), alemtuzumab (anti-CD52) (17) (146), abatacept (CTLA-4 agonist) (147), ruxolitinib (JAK inhibitor) (148), infliximab (TNFa antibody) (149), tofacitinib (JAK inhibitor) (150), mycophenolate mofitil (151), and antithymocyte globulin (152), and IV immunoglobulin. (153) However, the effectiveness of these therapies in ICI induced cardiac irAEs is unclear and they are therefore only reserved for patients with poor responses to corticosteroids.…”
Section: Novel Prophylaxis and Therapies For Cardiac Iraesmentioning
confidence: 99%